1999
DOI: 10.1590/s0001-37141999000200008
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of bacteriocin-producing Lactococcus lactis strains

Abstract: One hundred sixty seven strains of Lactococcus lactis were screened for bacteriocin production by well diffusion assay of GM17 agar. Fourteen (8.4%) produced antimicrobial activity other than organic acids, bacteriophages or hydrogen peroxide. The frequency of bacteriocin production ranged from 2% in L. lactis subsp. cremoris up to 12% in L. lactis subsp. lactis. Antimicrobial activities were not observed in any strain of L. lactis subsp. lactis var. diacetylactis. Among thirteen bacteriocin-producing strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
0
22
0
4
Order By: Relevance
“…In addition to minimizing the production of acids, the BHI used in this study received a solution of catalase to hydrolyze the hydrogen peroxide that may have been produced by the tested LAB cultures (Moreno, Lerayer, & Leitão, 1999;Schillinger & Lücke, 1989). Hydrogen peroxide is another substance with antimicrobial potential produced by LAB (Carr et al, 2002) and may interfere with the identification of antimicrobial activity from the production of bacteriocins or bacteriocin-like substances.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to minimizing the production of acids, the BHI used in this study received a solution of catalase to hydrolyze the hydrogen peroxide that may have been produced by the tested LAB cultures (Moreno, Lerayer, & Leitão, 1999;Schillinger & Lücke, 1989). Hydrogen peroxide is another substance with antimicrobial potential produced by LAB (Carr et al, 2002) and may interfere with the identification of antimicrobial activity from the production of bacteriocins or bacteriocin-like substances.…”
Section: Resultsmentioning
confidence: 99%
“…Moreno et al (18) reported that 8.4% of 167 strains of a culture collection were able to inhibit all the indicator microorganisms studied and Hastings et al (9) isolated five bacteriocin-producing lactic acid bacteria from 139 cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreno et al (1999) have isolated several strains of lactic acid bacteria from food products as cheese and milk. The antagonistic activity was detected through the well diffusion assay on agar plates (Toro, 2005).…”
Section: Isolation and Purificationmentioning
confidence: 99%